2006
DOI: 10.1177/0146167206287974
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Behavioral Persistence: The Self-As-Doer Construct

Abstract: Why do some people persist in goal pursuit, even in the face of boredom or setbacks, whereas others quickly give up their goals? In this research, the authors introduce a new motivational construct, the "self-as-doer," to explore this question. Studies 1 and 2 found longitudinal evidence that those who more strongly endorse doer statements regarding their goals (i.e., exerciser, dieter, runner) show greater behavioral persistence and attainment regarding such goals, even controlling for other relevant construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 20 publications
4
57
1
Order By: Relevance
“…The unique variance explained in the outcomes due to OSPHI was 6 percent to 13 percent beyond control variables of organizational tenure, gender, and organizational identification. This supports our contention that considering the self-as-doer (Houser-Marko & Sheldon, 2006) and the self-as-member provides an enhanced understanding of employee work outcomes in specific contexts. Grant et al (2008) demonstrated that prosocial identity and employee views of the organizationˈs prosocial identity predicted commitment toward beneficiaries.…”
Section: Theoretical Implicationssupporting
confidence: 85%
See 1 more Smart Citation
“…The unique variance explained in the outcomes due to OSPHI was 6 percent to 13 percent beyond control variables of organizational tenure, gender, and organizational identification. This supports our contention that considering the self-as-doer (Houser-Marko & Sheldon, 2006) and the self-as-member provides an enhanced understanding of employee work outcomes in specific contexts. Grant et al (2008) demonstrated that prosocial identity and employee views of the organizationˈs prosocial identity predicted commitment toward beneficiaries.…”
Section: Theoretical Implicationssupporting
confidence: 85%
“…Identity theory emphasizes the meanings that people apply to themselves based on the roles they assume (Burke, 1991). These identities reflect what Houser- Marko and Sheldon (2006) called the "self as doer" because roles beget action. Someone with a volunteer identity volunteers (Van Dyne & Farmer, 2005), and someone with a helping identity helps (Farmer & Van Dyne, 2010).…”
mentioning
confidence: 99%
“…When an interesting activity becomes so important that it contributes to one's identity or has the potential to do so in the future, individuals are more likely to become passionate about this particular activity. Indeed, enjoying science and having the perception that one may become a scientist later on (a possible self, Markus & Nurius, 1986 ) should make this potential identity element salient, thereby facilitating its internalization in identity (Houser-Marko & Sheldon, 2006 ) and the development of passion for this fi eld.…”
Section: On the Development Of Passionmentioning
confidence: 99%
“…The ability to persist on a task can be influenced by motivation traits like need for achievement and mastery motivation (Atkinson, 1960;Feather, 1963;Sigman, Cohen, Beckwith, & Topinka, 1987), the person's skill level, perception of task difficulty (Sigman et al, 1987), and self-perception (Houser-Marko & Sheldon, 2006). Two fundamental skills related to task persistence is the ability to focus attention on a task and the ability to handle mental effort and frustration (Deater-Deckhard, Petrill, & Thompson, 2007;Sigman et al, 1987).…”
Section: Attention Controlmentioning
confidence: 99%